229k views
5 votes
I need help please hekp

I need help please hekp-example-1
User FFox
by
5.4k points

1 Answer

0 votes

Answer:


\displaystyle y=(3)/(2)x^2-9x+(19)/(2)

Explanation:

Equation of the Quadratic Function

The vertex form of the quadratic function has the following equation:


y=a(x-h)^2+k

Where (h, k) is the vertex of the parabola that results when plotting the function, and a is a coefficient different from zero.

Substituting the coordinates of the vertex (3,-4):


y=a(x-3)^2-4

Now we find the value of a by substituting the point through which the function passes (1,2):


2=a(1-3)^2-4

Operating:


2=4a-4


4a=6


a=(3)/(2)

Thus, the equation is:


\displaystyle y=(3)/(2)(x-3)^2-4

Expanding the square:


\displaystyle y=(3)/(2)(x^2-6x+9)-4

Operating:


\displaystyle y=(3)/(2)x^2-9x+(27)/(2)-4

Simplifying:


\boxed{\displaystyle y=(3)/(2)x^2-9x+(19)/(2)}

User Agamagarwal
by
4.5k points